2007
DOI: 10.1016/j.cell.2007.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tRNA Nuclear Export Links DNA Damage and Cell-Cycle Checkpoint

Abstract: In response to genotoxic stress, cells evoke a plethora of physiological responses collectively aimed at enhancing viability and maintaining the integrity of the genome. Here, we report that unspliced tRNA rapidly accumulates in the nuclei of yeast Saccharomyces cerevisiae after DNA damage. This response requires an intact MEC1- and RAD53-dependent signaling pathway that impedes the nuclear export of intron-containing tRNA via differential relocalization of the karyopherin Los1 to the cytoplasm. The accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
82
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 50 publications
3
82
1
2
Order By: Relevance
“…We explored the possibility that growth in glycerol medium may influence expression or localization of Los1. It has been previously reported that Los1 is mislocalized to cytoplasm upon DNA damage, causing increased nuclear accumulation of intron-containing tRNA (47). We therefore examined localization of C-terminally Myc-tagged Los1 in control and maf1⌬ cells grown under standard (YPD) or restrictive (YPGly, 37°C) conditions (Fig.…”
Section: Saturation Of Nuclear Export Machinery In Maf1⌬-mentioning
confidence: 99%
See 1 more Smart Citation
“…We explored the possibility that growth in glycerol medium may influence expression or localization of Los1. It has been previously reported that Los1 is mislocalized to cytoplasm upon DNA damage, causing increased nuclear accumulation of intron-containing tRNA (47). We therefore examined localization of C-terminally Myc-tagged Los1 in control and maf1⌬ cells grown under standard (YPD) or restrictive (YPGly, 37°C) conditions (Fig.…”
Section: Saturation Of Nuclear Export Machinery In Maf1⌬-mentioning
confidence: 99%
“…Induction of Gcn4 Expression in maf1⌬ Cells-Both aberrant tRNA processing and limited tRNA export have marked effects upon the translation of the transcription factor, Gcn4 (47,48). Conditions that activate Gcn4 reduce the rate of general protein synthesis while simultaneously activating expression of proteins required under conditions of starvation and stress (reviewed in Ref.…”
Section: Saturation Of Nuclear Export Machinery In Maf1⌬-mentioning
confidence: 99%
“…While nature chose to link decoding to anticodon modification and codon usage in this yeast stress response, the possibility that other tRNA-related activities may be involved in other systems should be suspected. Of note are reports that alterations to tRNA processing, modification and subcellular transport can signal or result from stress, including MMS, nutrient deprivation and Elongator-sensitive zymocin toxicity 4,5,[9][10][11] . Although the chemical state of U34 and the decoding capacity of hypomodified tRNA Arg UCU and tRNA Glu UUC in trm9-∆ cells remain to be determined, the results point to exciting new means of genetic control.…”
mentioning
confidence: 99%
“…Although the chemical state of U34 and the decoding capacity of hypomodified tRNA Arg UCU and tRNA Glu UUC in trm9-∆ cells remain to be determined, the results point to exciting new means of genetic control. It will be interesting to know whether changes in the relative amount and/or decoding capacity of other subsets of tRNAs-as can occur via alterations in tRNA splicing, transport, modification or other processes [9][10][11] -are keyed to codon usage.…”
mentioning
confidence: 99%
See 1 more Smart Citation